Mechanisms of carcinogenic activity triggered by lysine-specific demethylase 1A - Chao Yang; Dan Li; Shaohong Zang; Lei Zhang; Zhangfeng Zhong; Yingtang Zhou (Frontiers Media S.A., 2022)
Epigenetics has emerged as a prime focus area in the field of cancer research. Lysine-specific demethylase 1A (LSD1), the first discovered histone demethylase, is mainly responsible for catalysing demethylation of histone 3 lysine 4 (H3K4) and H3K9 to activate or inhibit gene transcription. LSD1 is abnormally expressed in various cancers and participates in cancer proliferation, apoptosis, metastasis, invasion, drug resistance and other processes by interacting with regulatory factors. Therefore, it may serve as a potential therapeutic target for cancer. This review summarises the major oncogenic mechanisms mediated by LSD1 and provides a reference for developing novel and efficient anticancer strategies targeting LSD1.